"All's well with the fleet!" - Weston, H. J. (Harry John), 1874-1955 (Sydney : Australasian News Company, Limited, 1914)
A set of 12 colour lithographs, most signed in image, all titled below image, originally issued in printed wrappers fastened at one corner, designed to be detached, fragmented and displayed. The illustrations are cartoons on a naval theme, most showing a sailor and his (or somebody else's) lady, themed to a dozen ships, starting with HMAS Australia, which depicts a Jack Tar seaman and a Light Horse trooper throwing stones at a dachshund on a Pacific island. The names of the other ships are all British, chosen for comic effect, as in H.M.S. Triumph, where a sailor is triumphant over a soldier in getting his girl. The cover is embellished with a pipe-smoking naval rating sporting an eye-patch and a broad grin, wearing the cap of H.M.A.S. Sydney.
H.M.A.S. Australia -- H.M.S. Triumph -- H.M.S. Dreadnought -- H.M.S. Challenger -- H.M.S. Devastation -- H.M.S. Powerful -- H.M.S. Terrible -- H.M.S. Audacious -- H.M.S. Invincible -- H.M.S. Defiance -- H.M.S. Encounter -- H.M.S. Majestic.
Cover title.
Also available online
Bound with a silk cord through the top left hand corner.
Keywords: Australia. -- Royal Australian Navy -- Pictorial works; Australia. -- Royal Australian Navy -- Caricatures and cartoons; World War, 1914-1918 -- Humor, caricatures, etc; Sailors -- Australia -- Pictorial works; Australian